Next generation sequencing in genetic diagnostics - Pittman, Alan (Henry Stewart Talks, 2014)
Sanger sequencing, Next generation sequencing (NGS) technologies, Target enrichment, Analysis of NGS data – Neurogenetics, Applications of NGS technology in genetics diagnostics (Dementia diagnostic panel, Parkinson’s disease NGS diagnostic panel)